Citizen participation in decision-making: can one make a difference?. (10th June 2016) - Fitzgerald, Ciara; McCarthy, Stephen; Carton, Fergal; Connor, Yvonne O; Lynch, Laura; Adam, Frederic
Abstract: Big Data promises benefits for society as well as business. Do policy makers know how best to use this scale of data driven decision-making in an effective way for citizens? Citizen participation is portrayed in literature as a key component in policy decision-making. Yet, this decision-making process to date is often driven by other stakeholders such as scientific experts, academic institutions, national and international governing bodies, to name but a few. Furthermore, there is scant literature on the best way to create policy for new technology, taking into consideration the voice of the citizen. The prevailing question, therefore, is what extent does citizen participation in decision-making make a difference to shaping policy for technology? Our paper explores an experimental method for citizens to make a difference to European policy decision-making on the future of technology and the impact on society. Employing a case study of Irish citizens as part of the CIMULACT (Citizen and Multi-Actor Consultation on Horizon 2020) project this paper reports a new methodology for gathering citizens' perspectives on future decision-making policies on technology. The findings reveal key advantages and disadvantages to this methodology. This paper makes a number of contributions to both the academic and practitioner communities.